Acute hormonal responses following different velocities of eccentric exercise. (15th May 2013) - Libardi, Cleiton A.; Nogueira, Felipe R. D.; Vechin, Felipe C.; Conceição, Miguel S.; Bonganha, Valéria; Chacon‐Mikahil, Mara Patricia T.
Summary The aim of this study was to compare the acute hormonal responses following two different eccentric exercise velocities. Seventeen healthy, untrained, young women were randomly placed into two groups to perform five sets of six maximal isokinetic eccentric actions at slow (30° s−1) and fast (210° s−1) velocities with 60‐s rest between sets. Growth hormone, cortisol, free and total testosterone were assessed by blood samples collected at baseline, immediately postexercise, 5, 15 and 30 min following eccentric exercise. Changes in hormonal responses over time were compared between groups, using a mixed model followed by a Tukey's post hoc test. The main findings of the present study were that the slow group showed higher growth hormone values immediately (5·08 ± 2·85 ng ml−1, P = 0·011), 5 (5·54 ± 3·01 ng ml−1, P = 0·004) and 15 min (4·30 ± 2·87 ng ml−1, P = 0·021) posteccentric exercise compared with the fast group (1·39 ± 2·41 ng ml−1, 1·34 ± 1·97 ng ml−1 and 1·24 ± 1·87 ng ml−1, respectively), and other hormonal responses were not different between groups (P>0·05). In conclusion, slow eccentric exercise velocity enhances more the growth hormone(GH) response than fast eccentric exercise velocity without cortisol and testosterone increases.